2008
DOI: 10.1021/bi702106m
|View full text |Cite
|
Sign up to set email alerts
|

On the Interpretation of the Observed Linear Free Energy Relationship in Phosphate Hydrolysis: A Thorough Computational Study of Phosphate Diester Hydrolysis in Solution

Abstract: The hydrolysis of phosphate esters is crucially important to biological systems, being involved in, among other things, signaling, energy transduction, biosynthesis, and the regulation of protein function. Despite this, there are many questions that remain unanswered in this important field, particularly with regard to the preferred mechanism of hydrolysis of phosphate esters, which can proceed through any of multiple pathways that are either associative or dissociative in nature. Previous comparisons of calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
223
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 111 publications
(250 citation statements)
references
References 101 publications
26
223
1
Order By: Relevance
“…However, these works employed quite a low level of theory, and, as was also highlighted by (Hou & Cui, 2012), the Zn 2+ -Zn 2+ distance in these simulations increased to an unphysical value of as high as 7Á0 Å (Lopéz-Canut et al 2011), in sharp contrast to the crystal structure and also to data from Extended X-ray Absorption Fine Structure (EXAFS) and X-ray crystallography, which suggests little change in the binuclear Zn 2+ catalytic site during the course of the reactions catalyzed by AP and NPP (Bobyr et al 2012). In contrast to this, a more careful (but, as argued below, not yet fully reliable) study by (Hou & Cui, 2012) obtains a qualitatively similar phosphodiester TS in aqueous solution to that obtained by our earlier study (Rosta et al 2008), coupled with the more reasonable observation of a significant tightening of the TS in the enzyme active site (see also Luo et al 2012b).…”
Section: The Electrostatic Basis For Catalytic Promiscuity In the Alksupporting
confidence: 58%
See 4 more Smart Citations
“…However, these works employed quite a low level of theory, and, as was also highlighted by (Hou & Cui, 2012), the Zn 2+ -Zn 2+ distance in these simulations increased to an unphysical value of as high as 7Á0 Å (Lopéz-Canut et al 2011), in sharp contrast to the crystal structure and also to data from Extended X-ray Absorption Fine Structure (EXAFS) and X-ray crystallography, which suggests little change in the binuclear Zn 2+ catalytic site during the course of the reactions catalyzed by AP and NPP (Bobyr et al 2012). In contrast to this, a more careful (but, as argued below, not yet fully reliable) study by (Hou & Cui, 2012) obtains a qualitatively similar phosphodiester TS in aqueous solution to that obtained by our earlier study (Rosta et al 2008), coupled with the more reasonable observation of a significant tightening of the TS in the enzyme active site (see also Luo et al 2012b).…”
Section: The Electrostatic Basis For Catalytic Promiscuity In the Alksupporting
confidence: 58%
“…18 (and Fig. 11 of Rosta et al 2008), we were able to computationally reproduce the observed trend over a very wide range of rate constants. Our point is that the rate determining TS are very different for the different compounds considered in our LFER studies.…”
Section: Counterparts)mentioning
confidence: 80%
See 3 more Smart Citations